IoT based healthcare middleware - Mehedi, Adib; Tokee, Abid Hassan; Islam, Surovi; Miah, M. Saef Ullah (Association for Computing Machinery, 2020)
In recent times, personal medical information can be of great value in times of crisis. Persistent medical information and history can be lost during transitions or carelessness. The aim of this work is to propose a middleware that shall help transfer medical information of patient to doctors and health care facilities. It is designed to function and work as a bridge between different healthcare services. The functions used by the middleware are driven by means of Internet of things (IoT). On the situation used by us cellular phones and personal computers will be used to exchange and alter information. Each patient's individual social security number (SSN) or any other equivalent identification will be their patient-ID making it a more simple way to organize each patient's unique database which shall be enriched with their medical history from the time they are born. Data will be stored in cloud storage as well as embedded in the patient's device to ensure swift data retrieval. Data will be transferred from one device to another through web applications and mobile applications. The system will significantly decrease the communication gap between patients and doctors while guaranteeing superior data exchange between all parties involved. During emergency, it will first send basic information regarding the patient to the nearest ambulances. Secondly it will alert nearest hospitals, and thirdly, allowing users to send detailed and personal data to a specific doctors to ensure precise and accurate treatment.